Charge Recombination in Polaron Pairs: A Key Factor for Operational Stability of Blue‐Phosphorescent Light‐Emitting Devices. Issue 8 (1st July 2020) - Odinokov, Alexey; Osipov, Alexey; Oh, Juwon; Moon, Yu Kyung; Ihn, Soo‐Ghang; Lee, Hasup; Kim, Inkoo; Son, Won‐Joon; Kim, Sangmo; Kravchuk, Dmitry; Kim, Jong Soo; Kim, Joonghyuk; et al.
Abstract: Irreversible chemical reactions are responsible for limited operational lifetime of organic light‐emitting devices (OLEDs). These reactions are triggered by highly reactive polaron pairs present in the emissive layer of OLEDs. Fast recombination of the polaron pairs is, therefore, crucial for slow degradation and high stability of OLED materials. Here, a study of the formation and annihilation of close polaron pairs in binary mixtures of wide bandgap hosts and a series of blue‐phosphorescent Ir(III) complex dopants, including two novel compounds, is reported. OLED devices containing doped light‐emitting layer are fabricated, and their operational lifetimes are estimated. Although inaccessible in solid films, charge recombination kinetics inside the polaron pairs is measured in liquid solutions using nanosecond laser flash photolysis. Multiscale computer simulations are applied to connect experimental results in different media and predict recombination rates in the device, with proper account taken of the inner‐ and outersphere reorganization in nonpolar materials. Predicted rates correlate with measured operational lifetimes, which demonstrates the key role of polaron pairs in the OLED degradation process. The developed methodology is useful for the rational design of novel OLED materials with higher efficiency and stability. Abstract : Degradation of organic light‐emitting devices (OLEDs) depends on the recombination rate of the vulnerable polaron pairs inside the emitting layer. Computer simulations are able to predict recombination rates in the solid materials and connect them with experiments in solution, providing clues to the mechanism of OLED degradation and some hints for designing of more stable materials.